(3OjhGf GdjhSjs - (3GdMSf Hf eSYhO Hf eMeO, CHh Ydj, fhQ GdOjf GdjhSj,J (B1102 (3g` s
(3ChdgG (B:s
(3Ef Hjf GdZeGe hGdRgQ GdZrV` V doQnMei bOjeI hENGA s
(3BNQgG (B:s
(3hcd GeQF jheG SjLRi HeG CJi ef GdNjQ Hd jLRj Ydi cd efhi s
(3fSNI KGfjIs
(3hGdOjhGf LeY Ydi MQha GdoeYLe hoQJH Ydi JQJjH GdeTGQbI dMQha GdeYLes
(3hjdj GdOjhGf CQLhRI aj Gdabgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B252 s
Keywords: (3GdCOHs